13.5% flexible organic solar cells achieved by robust composite ITO/PEDOT:PSS electrodes. (December 2019) - Lei, Tao; Peng, Ruixiang; Huang, Like; Song, Wei; Yan, Tingting; Zhu, Liqiang; Ge, Ziyi
Abstract: Flexible ITO electrodes, as one of the earliest commercialized electrodes with high conductivity and transmittance, have shown great applicability for flexible organic solar cells (FOSCs). Here we fabricated FOSCs based on four types of PET/ITO substrates. The influence of the trace content of Zonyl in PH1000 on photovoltaic performances was carefully investigated. The PH1000 containing 6% EG and 1% Zonyl PH1000 was most favorable for transmittance, conductivity and surface morphology. Under the optimum condition, FOSCs based on PBDB-T-2F:IT-4F obtained a power conversion efficiency (PCE) of 11.3% with a short-circuit current density ( J sc ) of 19.12 mA/cm 2 . Meanwhile FOSCs based on PBDB-T-2F:Y6 achieved a PCE of 13.5% with J sc of 22.46 mA/cm 2, which was the highest PCE with ITO electrodes up to date. Moreover, the optimal FOSCs remained 75.2% of original PCE after 1000 bending cycles, indicating that the use of composite electrodes attributed to overcoming the brittleness of ITO. This work opens a new avenue to prepare all solution-processed FOSCs based on ITO composite electrodes with great efficiency and robustness. Highlights: A high efficiency of 13.5% of FOSCs based on PET/ITO was obtained by all solution processed method fabrication. Zonyl doping in composite electrode significantly influenced on surface morphology, element composition and efficiency. FOSCs demonstrated excellent mechanical flexibility, retaining around 75% of the original PCE after 1000 times bending cycles.